KESANTUNAN BERBAHASA DALAM INTERAKSI AKADEMIK MAHASISWA DAN DOSEN: KAJIAN PRAGMATIK DI UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Fanindia Luthfi Oksaoi; Eko Suroso (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study aims to describe the form of speech and politeness in Indonesian in the interaction between students and lecturers in the Master of Indonesian Language and Literature Education program at the University of Muhammadiyah Purwokerto. This study is based on a pragmatic perspective with reference to the principles of politeness put forward by Leech, which encompasses the maxims of wisdom, generosity, praise, humility, agreement, and sympathy. The method used in this study is qualitative descriptive with data collection techniques in the form of the method of watching through the tapping, free involving, recording, and recording methods. The research data is in the form of student and lecturer speeches obtained from online learning activities through Zoom Meetings and WhatsApp groups. The results of the study show that academic interaction between students and lecturers tends to use polite language, characterized by the use of subtle, polite expressions, and paying attention to the social context and communication situation. Four dominant types of politeness maxims were found, namely the maxim of praise, the maxim of humility, the maxim of wisdom, and the maxim of agreement. The maxim of praise is seen in the lecturer's appreciation of student achievements, the maxim of humility is shown through the attitude of humble students, the maxim of wisdom is seen in efforts to minimize losses for speech partners, and the maxim of agreement is reflected in the agreement between lecturers and students. Thus, this study shows that master's students have good pragmatic skills in applying the principle of language politeness. These findings are expected to be a reflection in improving the quality of effective, polite, and professional academic communication. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan bentuk tindak tutur dan kesantunan berbahasa Indonesia dalam interaksi antara mahasiswa dan dosen pada program Magister Pendidikan Bahasa dan Sastra Indonesia di Universitas Muhammadiyah Purwokerto. Kajian ini dilandasi oleh perspektif pragmatik dengan mengacu pada prinsip kesantunan yang dikemukakan oleh Leech, yang meliputi maksim kebijaksanaan, kedermawanan, pujian, kerendahan hati, kesepakatan, dan simpati. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan teknik pengumpulan data berupa metode simak melalui teknik sadap, simak bebas libat cakap, rekam, dan catat. Data penelitian berupa tuturan mahasiswa dan dosen yang diperoleh dari kegiatan pembelajaran daring melalui Zoom Meeting dan grup WhatsApp. Terdapat empat data yang diteliti yang menghasilkan maksim pujian, maksim kerendahan hati, maksim kebijaksanaan, dan maksim kesepakatan. Hasil penelitian menunjukkan bahwa interaksi akademik antara mahasiswa dan dosen cenderung menggunakan bahasa yang santun, ditandai dengan penggunaan ungkapan yang halus, sopan, serta memperhatikan konteks sosial dan situasi komunikasi. Dengan demikian, penelitian ini menunjukkan bahwa mahasiswa magister memiliki kemampuan pragmatik yang baik dalam menerapkan prinsip kesantunan berbahasa. Temuan ini diharapkan dapat menjadi bahan refleksi dalam meningkatkan kualitas komunikasi akademik yang efektif, santun, dan profesional.